Preliminary studies on parasitization potential of Braconid Wasp (Bracon hebetor Say) against certain Lepidopteran insect pest - Karthikeyan, A.; Pavithradevi, P.; Gavya, T.; Harini, K. (International Multidisciplinary Research Journal, 2022)
A study on parasitization percentage of Bracon hebetor Say on certain lepidopteran insect pest on Rice moth (Corcyra cephalonica Stainton), Tomato fruit borer (Helicoverpa armigera Hubner),Tobacco leaf eating caterpillar (Spodoptera litura Fabricius) and okra fruit borer (Earias vitella Fabricius), studied at ordinary room temperature under invitro conditions and revealed that C. cephalonica was the most suitable host for the development of B. hebetor among the host species tested regarding the parasitization percentage was high in C. cephalonica followed by S. litura, H. armigera and E. vitella.